Crossroads in Literature and Culture - Fabiszak, Jacek; Urbaniak-Rybicka, Ewa.; Wolski, Bartosz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book contains a selection of papers focusing on the idea of crossing boundaries in literary and cultural texts composed in English. The authors come from different methodological schools and analyse texts coming from different periods and cultures, trying to find common ground (the theme of the volume) between the apparently generically and temporarily varied works and phenomena. In this way, a plethora of perspectives is offered, perspectives which represent a high standard both in terms of theoretical reflection and in-depth analysis of selected texts. Consequently, the volume is addressed to a wide scope of both scholars and students working in the field of English and American literary and cultural studies; furthermore, it will be of interest also to students interested in theoretical issues linked with investigations into literature and culture.
Crossing thresholds of literary theories and critical approaches -- Remapping women$1 (Bs / men$1 (Bs moral and social borders -- Cross-language ventures -- Old world, new world and the space between -- Private territories, social spaces -- Across literary epochs, bringing together writers -- Extending the boundaries of genre and medium -- Countries and cultures at crossroads.s
Keywords: Linguistics; Sociolinguistics; Linguistics; Languages and Literature; Sociolinguistics